2014
DOI: 10.4236/ojpm.2014.44020
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Screen for Domestic Violence against Women in Healthcare Uganda: Associations with Demographic, Professional and Work Environmental Factors

Abstract: Aim: We assessed demographic, professional and work environmental determinants of readiness to screen for Intimate Partner Violence among healthcare practitioners in healthcare Uganda. Methods: The Domestic Violence Healthcare Provider Survey Scale and the Demand-Control-Support questionnaire was administered to a random sample of 376 health care providers (n = 279 valid responses) from Gulu, Anaka, Lacor and Iganga hospital situated in northern and eastern Uganda. Correlation tests, t-tests, ANOVA and Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…This association may be due to high representation of women in our study sample and women may show more readiness to screen for intimate partner violence out of sympathy for fellow women. Social workers perceived a higher self-efficacy than other providers which is consistent with studies conducted in Nigeria and Uganda that found Ugandan doctors had lower self-efficacy than other professions and social workers had higher self-efficacy (29,30). This differs from a Lebanese study that found that physicians considered themselves well positioned to manage intimate partner violence (31).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This association may be due to high representation of women in our study sample and women may show more readiness to screen for intimate partner violence out of sympathy for fellow women. Social workers perceived a higher self-efficacy than other providers which is consistent with studies conducted in Nigeria and Uganda that found Ugandan doctors had lower self-efficacy than other professions and social workers had higher self-efficacy (29,30). This differs from a Lebanese study that found that physicians considered themselves well positioned to manage intimate partner violence (31).…”
Section: Discussionsupporting
confidence: 78%
“…Confidence about referring a victim of intimate partner violence is an important component of the perceived support system, which in turn, is associated with an increased likelihood to screen for intimate partner violence (28)(29)(30)(31)(32). In our study, most participants were not confident about making referrals for abused women, which affected their proactivity to try and detect victims of intimate partner violence.…”
Section: Discussionmentioning
confidence: 64%
“…Our findings were in line with prior studies conducted in Uganda which showed that some healthcare workers in an urban-based OBGYN unit lacked technical competence to provide optimal ANC care to IPV survivors [41]. Similarly, one study conducted in Uganda by Lawoko and colleagues demonstrated that medical doctors had lower self-efficacy for IPV screening when compared to other healthcare professionals such as midwives [29].…”
Section: Discussionsupporting
confidence: 90%
“…Due to the complexity of risk factors and prevention strategies for IPV, systems-level interventions have been proposed. There is paucity of evidence from Low and Middle Income Countries (LMICs) [24,25], including Uganda, [26][27][28][29] that describes whether or how healthcare providers screen for IPV among populations of women seeking ANC services.…”
Section: Introductionmentioning
confidence: 99%
“…Shortened version of DVHPS is a universal and commonly used assessment tool to identify health care providers' readiness and impeding barriers to perform domestic violence screening in health care setting [10]. Previous studies indicated an acceptable psychometric evaluation for every item domain with Cronbach alpha ranging from 0.73 to 0.91 [11][12][13]. Also, study showed an averaged overall Cronbach alpha for all items domains of 0.88.…”
Section: Questionnaire Designmentioning
confidence: 99%